GERAKAN ANTI GLOBALISASI - Sonny Sudiar; Aisyah Aisyah; Muhammad Nizar Hidayat (Universitas Jenderal Ahmad Yani, 2018)
Globalization as a phenomenon that has been closely associated with 21st century is an interesting topic of discussion among academics and practitioners alike. The term is closely related with neo-liberalism paradigm in which it refers to an economic integration governed by the priciples of liberalization and openness. Even so, globalization did not occurr without resistance. Inequality resulted from the process of globalization has made some people struggle to resist it especially in the terms of economy. This article aimed to describe how globalization reshapes the world order and how it resulted to the anti-globalization movement that struggle to resist the inequality from the process of globalization.